Optimizing sewage water of Perum Pesona Permata Gading with the assistance of Cu/Mg electrodes as public street lighting based on green technology electricity - Rokhim, Deni Ainur; Smith, Diana Novel; Mukhtar, Alfredo Radinal; Koto, Azzahra Zafira Putri (Eclética Química, 2024)
Electricity in Indonesia uses fossil fuels as an energy source. If fossil fuels run out, we will lose our largest source of electrical energy. Therefore, we need a way to reduce dependence on fossil fuels by making good use of renewable energy as a source of electrical energy. One of them is Green Technology Electricity with the utilization of sewage water to convert chemical energy into electrical energy. This study aims to determine the potential of sewage water assisted by Cu/Mg electrodes as a source of street lighting, manufacturing, and testing methods, and the effect of optimizing sewage water on electrical performance as street lighting. Lack of lighting in residential areas is also a supporting factor in this research. The stages used are preparation, incubation, construction assembly, research, and strength testing. Based on research, the sewage water from Perum Pesona Permata Gading can be used as street lighting with the highest potential difference and current strength being 4.4 V and 0.55 A for each 50 mL of the sewage water.